2016
DOI: 10.1021/acs.jpcc.5b12391
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene Oligomerization over Pd Nanoparticles with Controlled Shape: A Parahydrogen-Induced Polarization Study

Abstract: Substantial signal enhancements achieved by using parahydrogen in catalytic hydrogenations are powerful tools for mechanistic studies of chemical reactions involving molecular H2. Potentially, this technique can be extended to other reaction classes, providing new information about reaction mechanisms. Moreover, this can lead to new substances with highly polarized spins. Herein, we report strong signal enhancements of oligomerization reaction products observed during the selective hydrogenation of acetylene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…In principle, sequential dehydrogenation–hydrogenation can also lead to the spin hyperpolarization if para-H 2 addition proceeds in a pairwise manner, as was reported previously. 8 , 11 , 19 , 20 This route of production of hyperpolarized substances is referred to in the literature as “pairwise replacement”. 19 , 20 Thus, propane dehydrogenation over VCAT may produce hyperpolarized propane.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, sequential dehydrogenation–hydrogenation can also lead to the spin hyperpolarization if para-H 2 addition proceeds in a pairwise manner, as was reported previously. 8 , 11 , 19 , 20 This route of production of hyperpolarized substances is referred to in the literature as “pairwise replacement”. 19 , 20 Thus, propane dehydrogenation over VCAT may produce hyperpolarized propane.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords Size-dependent · Nanoparticle · Melting · Enthalpy 1 Introduction Palladium nanoparticles have received growing interest due to their novel properties such as size (Chen et al, 2016) and shape (facet) (Wang et al, 2017) dependent catalytic activity, controlled oligomerization (Zhivonitko et al, 2016) and enhanced hydrogen storage (Rangel et al, 2016). However, due to the higher surface to volume ratio (Schmidt et al, 1998;Safaei et al, 2008), the nanoparticles are known as the most unstable structures among different nanosolids.…”
mentioning
confidence: 99%
“…The same group also found that the hydrogenation of acetylene over palladium nanoparticles of different morphologies (cubes, octahedra, and cuboctahedra) could also afford C 4 ‐oligomeric products (1,3‐butadiene, 1‐butene, and 2‐butene). Such oligomers exhibited high levels of polarization (up to 1.7 %) …”
Section: Heterogeneous Phipmentioning
confidence: 99%
“…Such oligomers exhibited high levels of polarization (up to 1.7 %). [153] The range of substrates that can produce PHIP effects is not limitedt ou nsaturated hydrocarbons. The hydrogenation reactions of a,b-unsaturated carbonyl compounds over various supported catalysts, [154] C 6 -cyclic compounds, [155] and furan derivatives over Rh/TiO 2 ,P d/TiO 2 ,P t/TiO 2 catalysts, [156] as well as the hydrodesulfurization of thiophene over MoS 2 /g-Al 2 O 3 and Pt/TiO 2 catalysts, [157] with parahydrogen have been performed.…”
Section: Heterogeneous Phipmentioning
confidence: 99%